Neonatal medicine in ancient art - Yurdakök, Murat (The Turkish Journal of Pediatrics, 2010)
There are a limited number of artistic objects from ancient times with particular importance in neonatal medicine. The best examples are figurines from ancient Egypt of Isis nursing Horus, showing the importance of breastfeeding. The earliest images of the human fetus were made by the Olmecs in Mexico around 1200- 400 BCE. One of the earliest representations of congenital anomalies is a figurine of diencephalic twins thought to be the goddess of Anatolia, dated to around 6500 BCE. In addition to these figurines, three sets of twins in the ancient world have medical importance, and Renaissance artists often used them as a subject for their paintings: "direct suckling animals" (Romulus and Remus), "heteropaternal superfecundation" (mother: Leda, fathers: Zeus, the king of the Olympian gods, and Leda's husband, Tyndareus), and "twin-to-twin transfusion" in monozygotic twins (Jacob and Esau).